Accelerated NMR Spectroscopy with Low-Rank Reconstruction - Qu, Xiaobo; Mayzel, Maxim; Cai, Jian-Feng; Chen, Zhong; Orekhov, Vladislav (Angewandte Chemie International Edition, 2015)
Accelerated multi‐dimensional NMR spectroscopy is a prerequisite for high‐throughput applications, studying short‐lived molecular systems and monitoring chemical reactions in real time. Non‐uniform sampling is a common approach to reduce the measurement time. Here, a new method for high‐quality spectra reconstruction from non‐uniformly sampled data is introduced, which is based on recent developments in the field of signal processing theory and uses the so far unexploited general property of the NMR signal, its low rank. Using experimental and simulated data, we demonstrate that the low‐rank reconstruction is a viable alternative to the current state‐of‐the‐art technique compressed sensing. In particular, the low‐rank approach is good in preserving of low‐intensity broad peaks, and thus increases the effective sensitivity in the reconstructed spectra. A low rank is an advantage: High‐quality NMR spectra are reconstructed from a small number of non‐uniformly sampled data points. Significant reduction in measurement time is obtained using the so far unexploited general property of NMR signal—its low rank (see picture; NUS=non‐uniform sampling).